Mestres e doutores no Brasil: uma análise empírica - (:unkn) unknown (Universidade Federal do Pampa, 2017)
The research analyzes the evolution of the masters and doctors, from 2011 to 2016. Thus, the economic theory of Human Capital is presented, as well as the evolution of postgraduate studies in Brazil and the scenario of the labor market, analyzed through the microdata provided by the Annual Report of Social Information - RAIS. The historical-inductive research method was used in conjunction with the econometric model of multiple linear regression to analyze the relationship between the level of schooling with two variables: salary and the employability of individuals. The results show that there is a correlation between educational level and wages, and in this sample of the population, the theory of human capital is confirmed, where the higher the educational levels, the higher the salaries.
Keywords: Capital humano; Mestres e doutores; Mercado de trabalho; Human capital; Masters and doctors; The labor market; CNPQ::CIENCIAS SOCIAIS APLICADAS